Climate Change Dry Spell Impact on Agriculture in Salyantar, Dhading, Central Nepal - Paudyal, Pramila; Bhuju, Dinesh Raj; Aryal, Manoj (Nepal Journal of Science and Technology, 2016)
Understanding the problem increasingly posed by climatic change is one of the critical challenges of our time. A study was carried out in Salyantar village in Dhading district of central Nepal to understand and assess the extent of climate change impacts on agriculture. The impact assessment was performed through analysis of meteorological data, Landsat images, and people’s perception on changes relative to agriculture sector. Mann-Kendall statistical trend test was used to assign statistical significance to the trend whereas temperature vegetation dryness index (TVDI) was used to identify soil moisture condition as an assessment criterion. The perception of local people on climate change and its impacts was studied through generalized questionnaire survey and participatory rural appraisal. The results of the study portrayed rise in temperature in the study area in the recent years in comparison to the past. The maximum temperature increment was 0.03p C per year. As for precipitation, it showed decreasing trend by 1.855mm per year. The TVDI obtained from Landsat image, showed decreasing trend of soil moisture in different years, which indicate an increased longer dry spell. This has unswerving effect on agriculture as the entire Salyantar village is dependent upon rain-fed agriculture. The perceived impacts on agriculture were decreased crop yield, reduced soil moisture, and increased incidence of new pests and invasive plant species. Such impacts were fairly heterogeneous in distribution. The Salyantar village, a raised flat-land of river deposition already stuck in the grip of water stress, was found exacerbated by the effect of climate change. Nepal Journal of Science and Technology Vol. 16, No.1 (2015) pp.59-68